A SWOT (strenghts, weaknesses, opportunities and threats) analysis on the use of focal persons as a mainstreaming strategy in combating HIV and AIDS in the public service of Namibia - Vatuva, Sircca Nelao Nangula (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil) -- Stellenbosch University, 2008.